2011
DOI: 10.1186/2047-783x-16-11-507
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of hard tissue related factors in the mouse dental pulp after immediate teeth separation

Abstract: We examined change of Runx2 and ALP expression in mouse tooth pulp which exposed to teeth separation experiment by immunohistochemistry as a model for conservative dentistry treatment. 8-week-old 36 male ddY mice were used and wedge was inserted between upper 1st and 2nd molars. The wedge was removed 30 minutes as well as 3 hours after the insertion and the samples were prepared extending up to 1 week of time period for regular histopathological and immunohistochemical examinations for ALP and Runx2 expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…In our previous studies, we induced the differentiation of dental pulp cells by adding injurious stimulation to the periodontium and pulp [10,11]. Nabeyama et al have shown that there is a weak positive reaction for Runx2 in the pulp tissue that has not been artificially stimulated [10]. This is similar to the results of the study conducted by Nakano et al [35,36], and it is presumed that it is a reaction to physiological stimuli, such as mastication and occlusion.…”
Section: Cell Differentiation Of Bmdcs Recruited To the Dental Pulpsupporting
confidence: 78%
See 4 more Smart Citations
“…In our previous studies, we induced the differentiation of dental pulp cells by adding injurious stimulation to the periodontium and pulp [10,11]. Nabeyama et al have shown that there is a weak positive reaction for Runx2 in the pulp tissue that has not been artificially stimulated [10]. This is similar to the results of the study conducted by Nakano et al [35,36], and it is presumed that it is a reaction to physiological stimuli, such as mastication and occlusion.…”
Section: Cell Differentiation Of Bmdcs Recruited To the Dental Pulpsupporting
confidence: 78%
“…Additionally, ALP expressed in the early stage of calcification associated with odontoblast differentiation is an index of odonoblastic activity [33]. In our previous studies, we induced the differentiation of dental pulp cells by adding injurious stimulation to the periodontium and pulp [10,11]. Nabeyama et al have shown that there is a weak positive reaction for Runx2 in the pulp tissue that has not been artificially stimulated [10].…”
Section: Cell Differentiation Of Bmdcs Recruited To the Dental Pulpmentioning
confidence: 99%
See 3 more Smart Citations